2016
DOI: 10.3389/fnut.2016.00039
|View full text |Cite
|
Sign up to set email alerts
|

Porcine Milk Oligosaccharides and Sialic Acid Concentrations Vary Throughout Lactation

Abstract: BackgroundMilk oligosaccharides (OSs) are bioactive components known to influence neonatal development. These compounds have specific physiological functions acting as prebiotics, immune system modulators, and enhancing intestine and brain development.ObjectivesThe pig is a commonly used model for studying human nutrition, and there is interest in quantifying OS composition of porcine milk across lactation compared with human milk. In this study, we hypothesized that OS and sialic acid (SA) composition of porc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 41 publications
4
47
0
Order By: Relevance
“…Milk from a number of animals, including cow (Albrecht et al 2014; Barile et al 2010; Tao et al 2008, 2009), sheep (Albrecht et al 2014, Martinez-Ferez et al 2006), goat (Albrecht et al 2014, Chaturvedi & Sharma 1988, Martin-Ortiz et al 2016, Martinez-Ferez et al 2006, Thum et al 2015), pig (Albrecht et al 2014, Mudd et al 2016, Salcedo et al 2016, Tao et al 2010), horse (Albrecht et al 2014, Nakamura et al 2001, Urashima et al 1991), and camel (Albrecht et al 2014, Alhaj et al 2013, Fukuda et al 2010), contains oligosaccharides similar to those found in human milk. There is a growing interest in examining the structures and concentrations of these animal milk oligosaccharides to identify additional sources of compounds with similar bioactivity to HMOs.…”
Section: Bovine Milk Oligosaccharides: Structures and Compositionmentioning
confidence: 96%
See 2 more Smart Citations
“…Milk from a number of animals, including cow (Albrecht et al 2014; Barile et al 2010; Tao et al 2008, 2009), sheep (Albrecht et al 2014, Martinez-Ferez et al 2006), goat (Albrecht et al 2014, Chaturvedi & Sharma 1988, Martin-Ortiz et al 2016, Martinez-Ferez et al 2006, Thum et al 2015), pig (Albrecht et al 2014, Mudd et al 2016, Salcedo et al 2016, Tao et al 2010), horse (Albrecht et al 2014, Nakamura et al 2001, Urashima et al 1991), and camel (Albrecht et al 2014, Alhaj et al 2013, Fukuda et al 2010), contains oligosaccharides similar to those found in human milk. There is a growing interest in examining the structures and concentrations of these animal milk oligosaccharides to identify additional sources of compounds with similar bioactivity to HMOs.…”
Section: Bovine Milk Oligosaccharides: Structures and Compositionmentioning
confidence: 96%
“…Relative abundances of acidic, acidic fucosylated, neutral fucosylated, and neutral nonfucosylated oligosaccharides in human, bovine, and porcine milk, as demonstrated by selected glycomics studies (Mudd et al 2016, Ninonuevo et al 2006, Tao et al 2009). …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…When purifying milk OS by PGC SPE, the solid phase is normally washed with water after sample loading (Mudd et al, 2016; Sundekilde et al, 2012; Tao et al, 2008), and water was therefore used as a control to the effectiveness of washing with low concentrations of ACN and TFA. TFA was included in all washing solutions to improve the recovery of acidic OS, as acidic pH increases the affinity of acidic OS for graphitised carbon (Pabst & Altmann, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Graphitised carbon solid phase extraction (SPE) is a well-established glycan purification technique that is commonly used in many glycomics workflows, including characterisation of protein N-glycomes (Aldredge, An, Tang, Waddell, & Lebrilla, 2012; Hua et al, 2013; Stumpo & Reinhold, 2010), biomarker discovery (Alley, Madera, Mechref, & Novotny, 2010; Balog et al, 2012; Vieira et al, 2012), and profiling of free milk OS (Marx et al, 2014; Mudd et al, 2016; Tao et al, 2008). Although previous publications have characterised the excellent retention characteristics of graphitized carbon in the context of glycan desalting and preconcentration (Packer, Lawson, Jardine, & Redmond, 1998; Redmond & Packer, 1999; Ward, 2009), the efficiency of the technique in separating milk OS and lactose has not been well-characterised, despite its widespread use for this purpose.…”
Section: Introductionmentioning
confidence: 99%